A GIS-based Study on the Distribution of Religious Buildings in Lhasa and its Historical Urban Spatial Pattern - Chi, Mengjie; Xu, Yinghao; Wang, Yan (International Planning History Society Proceedings, 2024)
This study examines the pivotal role of religious architecture in shaping Lhasa’s urban landscape, emphasizing Buddhism’s profound impact on the rise, development, and spatial organization of Tibetan cities. Religious architectures serve as essential nodes for public engagement with Buddhism and are central to the city’s socio-cultural fabric. Using Geographic Information Systems (GIS), the research quantitatively and qualitatively analyzes the distribution, density, and architectural characteristics of Lhasa’s religious edifices. This approach offers a comprehensive understanding of the spatial interplay between these religious sites and the broader urban matrix. By integrating Lhasa’s natural topography and socio-historical context, the study provides insights into how geographical and cultural factors influence urban planning and architecture. The objective is to delineate the spatial symbiosis between religious architecture and Lhasa’s urban form, revealing how these structures have shaped the city’s physical and cultural landscape. Through this multidisciplinary lens, the paper aims to contribute to the broader discourse on the intersection of religion, architecture, and urban development, particularly in historically and religiously significant cities.